2017
DOI: 10.1002/cld.680
|View full text |Cite
|
Sign up to set email alerts
|

Medication nonadherence in liver transplantation

Abstract: http://aasldpubs.onlinelibrary.wiley.com/hub/journal/10.1002/(ISSN)2046-2484/video/10-6-reading-whitsett.html a video presentation of this article http://aasldpubs.onlinelibrary.wiley.com/hub/journal/10.1002/(ISSN)2046-2484/video/10-6-interview-whitsett.html the interview with the author

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…This global improvement in graft failure and survival rates is most likely due to several factors, including either technological and surgical technique advancements or improvement in medical management and immunosuppressive therapy -it may not be necessarily due to improved medication adherence. (28)(29)(30)(31)(32)(33) Treatment for management of grafts consists of a combination of immunosuppressive agents with different mechanisms of action. This strategy minimizes morbidity and mortality individually associated to each immunosuppressive agent class, maximizing global treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This global improvement in graft failure and survival rates is most likely due to several factors, including either technological and surgical technique advancements or improvement in medical management and immunosuppressive therapy -it may not be necessarily due to improved medication adherence. (28)(29)(30)(31)(32)(33) Treatment for management of grafts consists of a combination of immunosuppressive agents with different mechanisms of action. This strategy minimizes morbidity and mortality individually associated to each immunosuppressive agent class, maximizing global treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…This intervention showed significant decrease in NA, stabilization of drug serum levels, and absence of liver, kidney, and heart complications. (13,(25)(26)(27)(28)(29)(30)(31)(32) Traditionally, when assessing NA in the setting of transplantation, one must correlate social and cultural factors to adherence findings. However, in this study, only one variable showed a certain level of relevance, marital status.…”
Section: Discussionmentioning
confidence: 99%
“…using pill bottles with a special cap that contains microelectronics to register the time and date of every bottle opening) yields detailed and reliable data but it is time- and cost-consuming[ 133 ]. There is also debate for its use as a gold standard, since it may not be feasible in clinical practice[ 134 , 135 ]. Trough levels can be affected by a variety of conditions, such as graft function and the concomitant use of other drugs[ 136 ].…”
Section: Maintenance Immunosuppression and Adherence To Therapymentioning
confidence: 99%
“…Liver transplant recipients (LTRs) are required to take immunosuppressive medications throughout their life. Nonadherence is common and is variable over time [ 1 ]. It is estimated that roughly 20–62% of adults and about 50% of pediatric LTR are nonadherent to their immunosuppressive medication regimen [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nonadherence is common and is variable over time [ 1 ]. It is estimated that roughly 20–62% of adults and about 50% of pediatric LTR are nonadherent to their immunosuppressive medication regimen [ 1 , 2 ]. The most serious outcomes of immunosuppression nonadherence (IMNA) include acute/chronic graft rejection and death.…”
Section: Introductionmentioning
confidence: 99%